2009
DOI: 10.1097/tp.0b013e31819cdddd
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Elderly Kidney Transplant Recipients are Related to Acute Rejection Episodes Rather Than Pretransplant Comorbidity

Abstract: Adequate immunosuppression with low frequency of rejection episodes improves the outcome for elderly kidney recipients as does a reduction of time on dialysis. CCI score at transplantation does not seem helpful in the selection of elderly patients for kidney transplantation but plays a significant role in patients under 70 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 25 publications
6
87
3
4
Order By: Relevance
“…The cohort age cutoff of Ն60 years was chosen in this study because this is consistent with prior reports (11)(12)(13)(14) and allowed sufficient power for multivariate analyses in each strata. To account for the age range in this elderly cohort, recipient age was stratified and included in each multivariate model.…”
Section: Methodsmentioning
confidence: 67%
“…The cohort age cutoff of Ն60 years was chosen in this study because this is consistent with prior reports (11)(12)(13)(14) and allowed sufficient power for multivariate analyses in each strata. To account for the age range in this elderly cohort, recipient age was stratified and included in each multivariate model.…”
Section: Methodsmentioning
confidence: 67%
“…Transplant outcomes improve with less dialysis time (71,72). In a Norwegian study, the worst outcomes were for patients older than age 70 with more than 1 year of dialysis (71). Survival was decreased for patients age 60-69 years with more than 1 year of dialysis, equivalent to the rate in patients older than age 70 with less than 1 year of dialysis (71).…”
Section: Transplantationmentioning
confidence: 99%
“…In a Norwegian study, the worst outcomes were for patients older than age 70 with more than 1 year of dialysis (71). Survival was decreased for patients age 60-69 years with more than 1 year of dialysis, equivalent to the rate in patients older than age 70 with less than 1 year of dialysis (71). Unfortunately, patients older than age 65 are less likely to receive a deceased-donor kidney within 1 year (73).…”
Section: Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have attempted to identify factors that would predict outcomes in elderly kidney transplanted recipients. Most recently, Heldal et al [47] found that acute rejection in the first 90 days, and donor age C60 years predicted lower patient survival; whereas delayed graft function, donors aged 60 years or older, and HLA antibodies were associated with increased death-censored graft loss. Gill et al [48] …”
mentioning
confidence: 99%